Teenage motherhood: where you live is also important. A prospective cohort study of 14, 000 women. (November 2016) - Wright, David M.; Rosato, Michael; Doherty, Rachel; O'Reilly, Dermot
Abstract: The United Kingdom has among the highest rates of teenage motherhood (TM) in Western Europe. The relationship to individual social and material disadvantage is well established but the influence of area of residence is unclear. We tested for additional TM risks in deprived areas or in cities. The Northern Ireland Longitudinal Study was used to identify 14, 055 nulliparous females (15–18). TM risk was measured using multilevel logistic regression, adjusting for health status, religion, family structure, socio-economic status, rurality and employment-based area deprivation. Most variation in TM was driven by individual, household and socioeconomic factors with the greatest proportion of mothers in low value or social rented accommodation. Living in an area with fewer employment opportunities was associated with elevated TM risk (most vs. least deprived, ORadj =1.98 [1.49, 2.63]), as was urban dwelling (urban vs. intermediate, ORadj =1.42 [1.13, 1.78]). We conclude that area of residence is a significant independent risk factor for TM. Interventions should be targeted towards the most deprived and urban areas and to those in the lowest value housing.